2021
DOI: 10.1002/jcla.24126
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum hemoglobin and major cardiovascular adverse event in Chinese patients with ST‐segment elevation myocardial infarction after percutaneous coronary intervention

Abstract: Background ST‐segment elevation myocardial infarction (STEMI) is a common clinical acute and severe disease, and it is of great significance to evaluate the prognosis of these patients. Hemoglobin levels are associated with a variety of diseases, but studies on Chinese patients with STEMI after percutaneous coronary intervention (PCI) have not been sufficient. Methods This was a secondary analysis based on a prospective cohort study of patients undergoing PCI in Taizhou, Zhejiang, China. We performed multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that the incidence of MACE is 10.9-30.5% if there is no related treatment among patients receiving PCI (23)(24)(25). Several therapies are recommended to prevent the incidence of MACE during the perioperative period of PCI according to the American College of Cardiology/AHA guidelines, among which statins serve a crucial role (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the incidence of MACE is 10.9-30.5% if there is no related treatment among patients receiving PCI (23)(24)(25). Several therapies are recommended to prevent the incidence of MACE during the perioperative period of PCI according to the American College of Cardiology/AHA guidelines, among which statins serve a crucial role (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Доказано, что риск MACE при ОИМ возрастает в 1,45 раз (95 % ДИ: 1,33-1,58) на каждый 1 г / дл снижения гемоглобина ниже 11 г / дл [27]. Пациенты с ИМпST, перенесшие ЧКВ, с низким уровнем гемоглобина до операции, были более склонны к развитию MACE, особенно если у них уже был ОИМ в анамнезе [28]. На данный момент отсутствуют валидированные рекомендации для инициации гемотрансфузии при ОИМ.…”
Section: Discussionunclassified